Schort communication. Effects of the plant growth stimulant SBPI on Bemisia tabaci Genn. (Homoptera: Aleyroridae) - Gomez, A.A.=700 1 Alonso, D.; Nombela, G.; Muñiz, M.
Es, En)
Ilus., 17 ref.
Keywords: TOMATE; INHIBIDORES DESARROLLO INSECTOS; BEMISIA TABACI; CULTIVO DE HORTALIZAS; REPRODUCCIO; ESPAÑA